Preparation of Ni/Bentonite Acid-Activated using Dragon Fruit Peel Extract (Hylocereus polyrhizus) As a Reductor for One Pot Synthesis of Menthol - Marhayuni, Yuni; Widiakongko, Priyagung Dhemi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Ni/Bentonite is acid-activated has been synthesized using dragon fruit peel extract (Hylocereus polyrhizus) as a reductor through an impregnation method. This research aims to characterize Ni/Bentonite acid-activated using dragon fruit peel extract as a reductor based on FTIR and XRD instruments and to analyze the product obtained in one pot synthesis of menthol from citronellal using Ni/Bentonite acid-activated catalyst. Preparation of Ni/Bentonite acid-activated catalyst was carried out using a wet impregnation method with dragon fruit peel extract as a natural reductor. The successful synthesis of Ni/Bentonite acid-activated was confirmed by FTIR spectrum identification, showing absorptions at wavelengths of 1049.28 cm?¹ and 694.37 cm?¹, indicating Si-O groups in the bentonite, and XRD diffractogram indicating the presence of Ni at diffraction peaks of 2? = 40.5° and 2? = 47.74°. The catalyst was able to convert menthol by 0.77% through one pot synthesis without using H? sources such as potassium formate.